2023
DOI: 10.1021/acs.langmuir.3c03529
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure Effect of PtCo Alloy with Adjustable Compositions for Efficient Methanol Electrooxidation

Xingqun Zheng,
Bin Wang,
Bingzhi Ren
et al.

Abstract: Various efficient strategies have been developed to overcome the anodic electrocatalyst issue of methanol-based fuel cells owing to their complicated methanol electrooxidation mechanism. In this work, PtCo nanoparticles with adjustable compositions supported on multiwalled carbon nanotubes (Pt 1 Co x /MWCNTs) through the adsorbing−coating−annealing− etching route were synthesized. Compared with the Pt/C catalyst, Pt 1 Co 3 /MWCNTs exhibit better electrocatalytic MOR activity in both activity and durability. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
0
8
1
Order By: Relevance
“…If inserting benzene ring resulted in a heterocyclic ring is missed in the structure, some N–(C) 3 linkages may miss and introduce certain defects, the content of N in N–(C) 3 should dwindled to certain degree. Our findings deviate from those reported data, which have overstated the ratio of N–(C) 3 to sp 2 N in in CN–C, due to casual fitting for XPS spectra. A higher ratio of N–(C) 3 indicates a higher degree of polymerization for PCN . If the ratio of sp 2 N in CN–C to N–(C) 3 were to reach 1.29, it implies the insertion of two benzene rings in three tri- s -triazine, contradicting their proposed structure for benzene-doped CNs.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…If inserting benzene ring resulted in a heterocyclic ring is missed in the structure, some N–(C) 3 linkages may miss and introduce certain defects, the content of N in N–(C) 3 should dwindled to certain degree. Our findings deviate from those reported data, which have overstated the ratio of N–(C) 3 to sp 2 N in in CN–C, due to casual fitting for XPS spectra. A higher ratio of N–(C) 3 indicates a higher degree of polymerization for PCN . If the ratio of sp 2 N in CN–C to N–(C) 3 were to reach 1.29, it implies the insertion of two benzene rings in three tri- s -triazine, contradicting their proposed structure for benzene-doped CNs.…”
Section: Resultscontrasting
confidence: 99%
“…However, the ratio of N–(C) 3 to sp 2 (C–NC) was calculated in an invalid way for the casual XPS spectra fitting. N 1s missed the peak of C–NH for benzene ring doped CN, while N 1s fitted the XPS spectra with unequal fwhm (full width at half maxim) . Yuan et al reported that benzene ring embedded in carbon nitride as electron acceptor .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overusing fossil fuels worldwide has sparked significant concern about environmental crises and climate change resulting from CO 2 emissions. To effectively address these challenges, the conversion of CO 2 into useful chemicals (such as CO, CH 4 , C 2 H 4 , and C 2 H 6 ) using sustainable and clean electronics under ambient conditions is of anxious demand. However, the high overpotential, poor selectivity, and inferior faradaic efficiency (FE) for the target products, along with competition from the hydrogen evolution reaction (HER), are the main obstacles that significantly hinder the current large-scale application of the CO 2 reduction reaction (CRR). Therefore, it is of great importance to explore an advanced CRR electrocatalyst with high selectivity and activity at a lower overpotential. , …”
Section: Introductionmentioning
confidence: 99%
“…The prerequisite for the practical application of this type of catalyst is to stably scatter metal atoms on supports that can strongly interact with the metal atoms to prevent their possible aggregation. 2D materials like graphene, boron nitrides, and transition metal dichalcogenides with unique physiochemical properties were widely investigated as substrates for metal atoms. However, metal atoms tend to diffuse and agglomerate on these substrates . Introducing vacancies and holes can solve this issue, but precisely carving and holding vacancies and holes are extremely difficult in large-scale applications .…”
Section: Introductionmentioning
confidence: 99%